Effect of Aromatase Inhibitors in the Treatment of Endometrial Hyperplasia in Post Menopausal Women (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To explore the effect of aromatase inhibitors in the treatment of endometrial hyperplasia in post menopausal women.Materials and Methods: This observational longitudinal study was undertaken in 21 postmenopausal women diagnosed as having endometrial hyperplasia in a private clinic in Dhaka between July, 2009 to January 2014. Initially hyperplasia was diagnosed by thickened endometrium by ultrasound and confirmed by histopathologic examination of fractional curretage. Among the patients, 7 had complex hyperplasia without atypia; 14 had simple hyperplasia without atypia. All the patients were treated with letrozole 2.5 mg per day for 12 months and were monitored by transvaginal ultrasonogram every 3 months, subsequently followed up by history and transvaginal ultrasonogram 6 monthly for another 12 months. Main outcome measure was reduction of endometrial thickness. Informed written consent was obtained before enrollment in the study.Results: Mean endometrial thickness decreased by 81.66% following 12 months of treatment and the endometrial thickness was not increased in next 12 months follow up period. All patients were symptom free during this treatment.Conclusion: The results of this study indicate that treatment of endometrial hyperplasia with aromatase inhibitors can reduce endometrial thickness. So, aromatase inhibitors deserve attention for the conservative treatment of endometrial hyperplasia.Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 78-82